Artemis Fowl : The Atlantis Complex - Book 7 The Atlantis Complex - Colfer, Eoin. (New York : Disney/Hyperion Books, 2010)
Teenaged criminal mastermind Artemis Fowl must save the underwater fairy metropolis of Atlantis from danger, while battling a psychological affliction known as the Atlantis Complex.
Keywords: Space and time -- Fiction; Fairies -- Fiction; Magic -- Fiction; Mental illness -- Fiction; Demonology -- Fiction; Atlantis (Legendary place) -- Fiction; Fiction